Behavioural analysis of factors influencing online food ordering and its relation to obesity - Labib, S. M. Fazle Rabby; Achol, Fahmida Zaman; Jawwad, Md. Aqib (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.